CHALLENGES FACED BY MULTINATIONAL CORPORATIONS IN NAVIGATING LEGAL FRAMEWORKS, CULTURAL DIFFERENCES, AND ETHICAL ISSUES IN DEVELOPING COUNTRIES [TANTANGAN YANG DIHADAPI PERUSAHAAN MULTINASIONAL DALAM MENGHADAPI KERANGKA HUKUM, PERBEDAAN BUDAYA, DAN ISU ETIKA DI NEGARA BERKEMBANG] - Hayatul Khairul Rahmat (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
Multinational corporations (MNCs) face various challenges when operating in developing countries, particularly regarding varying legal frameworks, cultural differences, and complex ethical issues. In these environments, companies must ensure compliance with international laws while respecting local customs. The biggest challenges include differences in data privacy regulations, such as the General Data Protection Regulation (GDPR) in the European Union and the Foreign Corrupt Practices Act (FCPA) in the United States. Additionally, significant cultural differences in communication styles and business etiquette between high-context and low-context cultures complicate operations. Ethical issues, such as gift-giving or facilitation payments that are considered unethical under international standards, add to the dilemma. Therefore, multinational companies must develop robust compliance policies, enhance cultural intelligence, and ensure adherence to global ethical principles to succeed in international markets.